The Colombian Education System: Challenges from the Curriculum and the Learning Process during the Pandemic - Mejía Cordero, Isbelia Arlenys (2023)
The last three years have been strongly affected by a worldwide situation, the COVID-19 pandemic, a crisis that especially marked educational processes and, specifically, student learning. Therefore, this document presents the curricular models in force in the Colombian education system, the reference documents of educational quality in Colombia, and a review of the public policies implemented during the confinement due to the pandemic. It is possible to identify the challenges that have been generated as a result of the COVID-19 pandemic in the educational field. Thus, through the information gathered, it is concluded that, although Colombia was not prepared to face this situation, it assumed the challenge of continuing with quality education, and despite the gaps and barriers encountered, the government promoted public policies that covered all educational levels.